Dynapenia syndrome in geriatrics – clinical characteristics, distinction from sarcopenia, and contemporary therapeutic approaches - Malon, Paulina; Śliwa, Karol; Pieńkowska, Anita; Trojańska, Aleksandra; Geworkian, Nel; Hariasz, Natalia; Pietz, Martyna; Szymańska, Anita (Journal of Education, Health and Sport, 2026)
Introduction Dynapenia is an age-related loss of muscle strength despite preserved muscle mass, leading to functional decline, loss of independence, falls, and higher mortality. Its development is influenced by neuromuscular, endocrine, and metabolic changes, compounded by chronic inflammation, low activity, and inadequate nutrition. Results Resistance training is the most effective strategy to mitigate strength loss, enhancing neuromuscular function and physical performance. Aerobic exercise improves endurance and mobility. Adequate protein intake (1.0–1.2 g/kg) and supplementation with vitamin D, creatine, leucine, and omega-3 fatty acids support training adaptations. Early detection via handgrip strength allows timely interventions. Discussion Combining targeted exercise with optimal nutrition and supplementation maintains strength and independence in older adults. Interventions should be individualized based on health and functional status. Emerging molecular and gene-based therapies are experimental but may complement lifestyle approaches. Conclusion Dynapenia is not inevitable with aging. Early recognition, regular training, and proper nutrition can slow strength loss, reduce fall risk, and improve well-being. Materials and methods A review of scientific articles from PubMed, Google Scholar, and Dove Press Medical focused on dynapenia, muscle aging, and physical and nutritional interventions in older adults.